Effect of 8 Week Consumption Flax Seed Supplementation with Endurance Training on BDNF and IGF-1 in Obese Women - A.R Pazoki; S Arshadi (Institue of Medicinal Plants, ACECR, 2019)
Background: Obesity and weight gain can cause health risks for people with metabolic disorders. Endurance activities and some herbal supplements can reduce the risks of metabolic syndrome by affecting hormonal indices and body weight. Objective: The present study examined the effect of 8 weeks of endurance training and supplementation of flax seed on BDNF and IGF-1 in obese women. Methods: 48 female obese 30-40 years old were selected and randomly divided into four groups: control (Con), endurance training (ET), supplemented flax seed (Sup) and combination (endurance training + Supplementation of flax seed (ET + Sup)). Endurance training included 8 weeks of increasing activity with an intensity of 30% to 70% of VO2 max. Flax seed supplements were consumed in powdery form at a dose of 6 g per day. T-test and one way ANOVA were used for statistical analysis. The turkeychr('39')s post hoc test was used at the level of 0.05. Results: Body weight showed a significant change in exercise, exercise + supplementation groups. The results of significant increase in BDNF showed a significant decrease in IGF-1 in both ET and ET + Sup groups compared to Con and Sup (P≤0.05). But the difference between the ET and ET + Sup groups was not significant. Conclusion: The findings of this study showed that aerobic training with flaxseed can be more effective in reducing body weight and improving metabolic parameters in obese women. These effects were associated with an increase in BDNF and a decrease in IGF-1 levels.